THE INFLUENCE OF PRE-HERBICIDE FERTILIZING WITH MINERAL FERTILIZERS ON THE STRUCTURE OF CROPS AND THE YIELD OF CHICKPEA (CICER ARIETINUM) - Turdieva Nilufar Mominovna; Mamadaliev Shavkatbek Pulatbekovich; Kalandarova Maftuna Majitovna; Umarov Akbar Aloevich; Yuldoshev Abdulaziz Abdumalikovich; Dilnura Tog'aeva Akbarovna; Shoxrux Tog'aev Akbarovich (Web of Journals Publishing, 2024)
Weeds reduce crop yields and worsen product quality. With average weediness, the yield is reduced by 20-25%, and with weak weediness it will not work at all.